Fishing Game Innovation as a Strategy for Developing Fine Motor Skills and Concentration in Early Childhood - Pahrul, Yolanda; Ayuni, Despa; Rosandi, Adinda Salsabila (STIT Ahlussunnah Bukittinggi, 2025)
The development of fine motor skills and concentration are crucial aspects for promoting optimal development in early childhood. However, effective, enjoyable, and affordable stimulation strategies remain a challenge in educational practice. This study aims to examine the effectiveness of a fishing game on improving children's fine motor skills and concentration. The research design used a pretest–posttest experiment with one experimental group and a control group. The instruments were fine motor observation and concentration tests, with data analysis using the Wilcoxon test using JASP. The results showed a significant increase between the pretest and posttest in fine motor skills (p = 0.001 < 0.05) and concentration (p < 0.001 < 0.05), thus the fishing game is proven to be effective in supporting early childhood development. The novelty of this study is the proof of the benefits of the fishing game not only on concentration as in previous studies, but also on fine motor skills. These findings provide empirical contributions and practical implications for educators and parents in utilizing simple games as a medium for stimulating child development.